Prevalence and incidence of prescription opioid analgesic use in Australia - Lalic, Samanta; Ilomäki, Jenni; Bell, J. Simon; Korhonen, Maarit Jaana; Gisev, Natasa (British journal of clinical pharmacology, 2019)
Aims The aims of the current study were to determine the prevalence and incidence of prescription opioid analgesic use in Australia and compare the characteristics of people with and without cancer initiating prescription opioid analgesics. Methods A retrospective population‐based study was conducted using the random 10% sample of adults who were dispensed prescription opioid analgesics in Australia between July 2013 and June 2017 through the Pharmaceutical Benefits Scheme. Poisson regression was used to calculate rate ratios (RR) for opioid prevalence and incidence. The characteristics of people initiating opioids, including type of opioid initiated, total oral morphine equivalents dispensed, prescriber speciality, medical comorbidities, and past analgesic and benzodiazepine use, were compared for people with and without cancer. Results Opioid prevalence increased {RR = 1.006 [95% confidence interval (CI) 1.004, 1.008]}, while incidence decreased [RR = 0.977 (95% CI 0.975,0.979)] from 2013/2014 to 2016/2017. There were between 287 677 and 307 772 prevalent users each year. In total, 769 334 adults initiated opioids between 2013/2014 and 2016/2017, and half of these initiations were by general practitioners. Initiation with a strong opioid occurred in 55.8% of those with cancer and 28.2% of those without cancer. Conclusion Rates of opioid use have remained high since 2013, with approximately 3 million adults using opioids and over 1.9 million adults initiating opioids each year. Between 2013 and 2017, opioid prevalence has slightly increased but incidence has decreased. People without cancer account for the majority of opioid use and are more likely to be initiated on short‐acting and weak opioids. Initiation of strong opioids has increased over time, reinforcing concerns about increased use and the harms associated with strong opioids in the community.